Be optimistic or be cautious? Affective forecasting bias in allocation decisions and its effect - Liu, Lei; Sun, Wujun; Fang, Ping; Jiang, Yuan; Tian, Li (Frontiers in Psychology, 2022)
People's forecasts of their future emotions play an important role in their behavior and experience of well-being. However, their emotional reactions may fall short of what they expect, which has implications for subsequent decision making. The current paper investigated the accuracy of affective forecasting about resource allocations, and the ways in which this (in)accuracy predicts future allocation decisions. Study 1 examined the extent to which people can accurately predict how allocation decisions will feel in an ultimatum game, finding that there is an affective forecasting bias and people anticipate more powerful emotional reactions to both positive and negative allocation events than they actually experience when the events occur. Study 2 tested whether the affective forecasting bias affects future allocation decisions in the ultimatum game, finding that increased affective forecasting bias results in less generous decisions in positive event conditions and more generous decisions in negative event conditions. These results extend previous findings concerning affective forecasting bias and the feelings-as-information model in resource allocation interactions, and show that the difference between anticipated and experienced emotion is also informative in allocation decisions. The results suggest that being more cautious when forecasting positive outcomes and more optimistic when forecasting negative outcomes can be beneficial to one’s well-being.